â€œKORBAN DAN KUASAâ€ DI DALAM KAJIAN KEKERASAN TERHADAP PEREMPUAN - Dwiningtyas Sulistyani, Hapsari (Faculty of Social and Political Sciences Diponegoro University, 2011)
Abstract:Most of gender studies on violence against women are mainly concerned with the way in which women are the victim of patriarchal power domination. Even though researches and studies on women as a victim are still important, it is also necessary to start looking at the potency of women in gaining the power and challenging their position as a victim. This paper shows the possibilities of shifting the dominant perspective on women studies.Exploring women's writing is one way of seeking alternative point of views that are able to challenge the patriarchal domination on the social construction of women.Key words: gender, women's writing, power-relation, victimpermalink:Â http://ejournal.undip.ac.id/index.php/forum/article/view/3153